Microwave Assisted Synthesis and Antimicrobial Evaluation of Schiff Bases of Indole-3-aldehyde - Priyanka Kamaria; N. Kawathekar; Prerna Chaturvedi (E-Journal of Chemistry)
In order to develop new antimicrobial agents, a series of Schiff bases of indole-3-aldehyde were synthesized by microwave assisted synthesis by taking DMF as solvent and evaluated for their antimicrobial activity. All the synthesized compounds were characterized by IR, 1HNMR and mass spectral analysis. All compounds were tested against five gram positive and five gram negative bacterial strains and one fungal strain. All compounds exhibited better activity against gram positive strains than against gram negative strains and the compounds were found more active against S.aureus and B.subtilis.